Investigation of Failure Mechanisms in the U-Bend Tubes of Shell and Tube Heat Exchangers - Achyarsyah, Mochamad; Hanaldi, Kus; Purwadi, Wiwik; Hermana, Gita Novian; Siswanto, Ari; Ruskandi, Cecep; Nadi, Muhammad Rizki Gorbyandi (National Research and Innovation Agency (BRIN), 2024)
The U-bend tubes of a shell-and-tube heat exchanger made of SA-234 Grade WPB carbon steel failed prematurely within 14 days after replacement and welding. This study investigates failure mechanisms through an integrated failure analysis that includes visual inspection, dye penetrant testing, chemical composition analysis, hardness measurements, and microstructural characterization. The results reveal that the tube contained 0.324 wt.% C, exceeding the maximum limit specified by the standard, which promoted the formation of Widmanstätten ferrite and reduced toughness. The welded joint exhibited multiple defects, including porosity and lack of fusion, which acted as stress concentration sites. Hardness measurements showed average values of 205 HV in the weld metal, 199 HV in the HAZ (heat-affected zone), and 184 HV in the base metal. Under operating conditions of 275 °C and 58.48 barg, these defects progressively opened, leading to fluid leakage. The escaping high-pressure fluid accelerated erosion-corrosion, as evidenced by oxygen-rich corrosion products detected by EDS analysis. The findings demonstrate that the combined effects of material non-compliance, poor welding quality, and unfavorable microstructural evolution governed the premature failure. This study provides quantitative insights to improve welding practices and material selection, thereby enhancing the reliability of U-bend tubes in shell-and-tube heat exchangers.